(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article presents the construction scheme and the principle of operation of the conveyor for transporting and cleaning cotton with two screw, strap element supports. Calculation scheme and mathematical model of two-screw and belt-supported shaft vibrations were obtained, and the expression for calculating the vibration amplitude was obtained. Connection graphs are presented for different modes of operation, taking into account the number of strap support singularities and dissipative coefficients. Based on the analysis, the recommended values ​​of the parameters were determined.